On the complexity of fixed parameter clique and dominating set - Eisenbrand, Friedrich; Grandoni, Fabrizio (Theoretical computer science, 2004)
We provide simple, faster algorithms for the detection of cliques and dominating sets of fixed order. Our algorithms are based on reductions to rectangular matrix multiplication. We also describe an improved algorithm for diamonds detection.